2019
DOI: 10.2478/ohs-2019-0020
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition products of cylindrospermopsin – a cyanotoxin produced by Raphidiopsis raciborskii (Woloszynska)

Abstract: Toxins produced by cyanobacteria (cyanotoxins) and released into water have become a serious problem worldwide due to the increasing morbidity and mortality of living organisms they have caused. The ability to synthesize the cytotoxic alkaloid cylindrospermopsin (CYN) has been demonstrated in several freshwater species of cyanobacteria. CYN is highly chemically stable under environmental factors and decomposes only under alkaline conditions, where it forms derivatives. The toxicity potential of the decompositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In other works, it was confirmed that L. trisulca also demonstrated the ability to degrade adsorbed ANTX-a [ 13 ], and another species of Lemna—L. minor exhibited the ability to eliminate MC-LR from water enriched with it, and L. gibba showed MC-LR accumulation from toxic Microcystis culture extract [ 12 , 56 , 57 ]. In comparison to these two toxins, little is known about CYN phytoremediation by macrophytes, and current studies are mainly based on the biodegradation of this compound by microorganisms such as Aeromonas sp.…”
Section: Resultsmentioning
confidence: 88%
“…In other works, it was confirmed that L. trisulca also demonstrated the ability to degrade adsorbed ANTX-a [ 13 ], and another species of Lemna—L. minor exhibited the ability to eliminate MC-LR from water enriched with it, and L. gibba showed MC-LR accumulation from toxic Microcystis culture extract [ 12 , 56 , 57 ]. In comparison to these two toxins, little is known about CYN phytoremediation by macrophytes, and current studies are mainly based on the biodegradation of this compound by microorganisms such as Aeromonas sp.…”
Section: Resultsmentioning
confidence: 88%